GAMBARAN KESIAPSIAGAAN BENCANA BANJIR PADA MASYARAKAT: LITERATURE REVIEW - Remon Pardamean Simanjuntak; Hellena Deli; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Introduction: Disasters in Indonesia are dominated by hydrometeorological disasters, flooding is a disaster with the greatest prevalence which has an impact on many problems. To anticipate the impact of flood, precautionary measures are the main focus of disaster management. Purpose: To describe flood disaster preparedness in communities in various places through existing literature. Method: The method used is a literature review study obtained from searching for research articles using the keyword Preparedness of floods and the community 2016-2020. Data source: Science Direct & Pubmed. Result: Based on the analysis and review of articles from 6 research journals, the community's preparedness was still not good. This result is due to several main factors, namely socioeconomic, local government assistance, and the age of the respondents who stated that the average age of 46 years and over has a better preparedness level Conclusion: From the 6 research journals reviewed, 1 journal was found discussing community preparedness related to the warning system. in the community, 6 journals discuss the level of community preparedness, factors that affect community preparedness, and preparedness actions. Recommendation: Cooperation in various lines or sectors is needed to overcome various obstacles in carrying out flood preparedness in the community.Keywords: Disaster, flood, community preparedness.